EMOTIONAL QUOTIENT PADA TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA JURUSAN AKUNTANSI - Ilham, Syarif Muhammad; Sastrawan, Rahman; Hendreo, Chornolius (JURNAL LENTERA AKUNTANSI, 2025)
This study aims to analyze the influence of emotional quotient (EQ) on the level of accounting understanding among students of the Accounting Department of PSDKU Pontianak State Polytechnic, Sanggau Campus. EQ is measured through five dimensions, namely self-awareness, self-management, motivation, empathy, and social skills. The research method used a quantitative approach by distributing questionnaires to 70 respondents, but only 54 data were suitable for processing. Data analysis was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique through SmartPLS 3.0 software. The results showed that self-awareness, motivation, and social skills had a significant positive effect on accounting understanding, while self-management and empathy had no significant effect. The coefficient of determination (R²) value of 0.508 indicates that the EQ variable is able to explain 50.8% of the variation in students' accounting understanding. This finding emphasizes the importance of developing emotional aspects, especially motivation and social skills, in improving the academic competence of accounting students.